2019
DOI: 10.32615/bp.2019.037
|View full text |Cite
|
Sign up to set email alerts
|

Cerium nitrate improves salt tolerance of wheat seedlings by regulating the antioxidant capacity of chloroplasts

Abstract: The effects of Ce(NO 3) 3 on the antioxidant capacity in the chloroplasts of salt-stressed wheat (Triticum aestivum L.) seedlings were investigated. The results showed that salt stress (40, 80, 120, or 160 mM NaCl) significantly increased the activities of ascorbate peroxidase, glutathione reductase, superoxide dismutase, catalase, and glutathione peroxidase, the content of malondialdehyde (MDA) and hydrogen peroxide (H 2 O 2), but significantly reduced the ratios of reduced ascorbate (AsA) to dehydroascorbate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
(22 reference statements)
2
3
0
Order By: Relevance
“…For this study, we found that salt stress significantly reduced Chl and Car contents, P n , T r , g s and RWC of strawberry leaves, which was consistent with previous studies (Yang and Lu 2005, Faghih et al 2017, Avestan et al 2019, Zahedi et al 2019. Chen and Shan (2019) have reported that Ce increased Chl and Car contents, as well as water physiological parameters P n in wheat leaves under salt stress. However, there is still no report on the effects of Ce on water physiological parameters of strawberries under salt stress.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…For this study, we found that salt stress significantly reduced Chl and Car contents, P n , T r , g s and RWC of strawberry leaves, which was consistent with previous studies (Yang and Lu 2005, Faghih et al 2017, Avestan et al 2019, Zahedi et al 2019. Chen and Shan (2019) have reported that Ce increased Chl and Car contents, as well as water physiological parameters P n in wheat leaves under salt stress. However, there is still no report on the effects of Ce on water physiological parameters of strawberries under salt stress.…”
Section: Discussionsupporting
confidence: 92%
“…Increasing evidence showed that many exogenous chemicals improved the salt tolerance of plants, such as hydrogen sulfide and rare earth elements (REEs) (Chen and Shan 2019, Li et al 2020). Among REEs, scandium (Sc), lanthanum (La) and cerium (Ce) have been shown to enhance the salt tolerance of plants (Huang and Shan 2018, Chen and Shan 2019, Elbasan et al 2020. For Ce, its role in improving salt tolerance has been studied on many crops, including food crop maize, cash crop cotton and fruit crop grapevine, etc.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been documented that the function of chloroplasts was closely related with the antioxidant capacity and the contents of photosynthetic pigments (Chen and Shan 2019). For the present study, our results clearly showed that Nd partly alleviated the negative effects of Cr on the contents of photosynthetic pigments Chl and Car.…”
Section: Discussionsupporting
confidence: 75%
“…Cd mainly accumulates in the roots of plants [6,7], which interferes with the growth and nutrient acquisition through the regulation of the rhizosphere environment [8]. When the Cd accumulates to toxic levels, severe physiological and biochemical disorders will be induced such as disturbances of nutrient absorption and transport which ultimately leads to production reduction [9]. Deficiency of any nutrient can cause obvious symptoms (such as chlorosis) and may be harmful to plants [10].…”
Section: Introductionmentioning
confidence: 99%